Comparative Analysis on Seismic Base Isolation for Integrated Fast Reactor Nuclear Power Plant - MIAO Xin, ZHANG Botao, LIU Yizhe, LIU Linding (Yuanzineng kexue jishu)
The fast reactor is one of the principal reactor types in the fourth generation of nuclear power technologies worldwide. The integrated closed-cycle fast reactor nuclear energy system (referred to as the integrated fast reactor) is a nuclear energy system co-located within a single site. This system integrates the fast reactor, fuel regeneration subsystem (including spent fuel reprocessing and new fuel fabrication), and other supporting subsystems, achieving self-sustaining circulation of nuclear fuel within the site. To enhance the design ultimate safety ground motion of the integrated fast reactor and expand its site applicability, base isolation technology was introduced. Given the unique structural characteristics of the integrated fast reactor nuclear island plant, such as its large mass and high stiffness, customized parameters for lead rubber bearings were developed. These bearings were subsequently employed in the base isolation design of the nuclear island plant, aiming to increase the ultimate safety ground motion from 0.2g to 0.4g. The isolated and aseismic nuclear island plant was modeled and analyzed using ETABS software. Based on the time history analysis method, the safety of the isolated nuclear island plant structure was evaluated, and the seismic isolation effects, as well as the floor response spectrum under different elevations and seismic acceleration inputs, were systematically studied. The analysis results demonstrate that the safety performance of the isolation layer, designed using the developed lead rubber bearings, complies with the requirements of the relevant specifications. The horizontal seismic isolation effect of the nuclear island plant is significant. For frequencies above 1 Hz, the horizontal floor response spectrum of the non-isolated structure can envelop that of the isolated structure, indicating effective seismic energy dissipation. Considering the seismic resistance of the equipment, the isolation system meets the original horizontal seismic isolation design objectives. Furthermore, the isolation scheme itself does not significantly amplify the vertical seismic response of the nuclear island plant. The primary factor contributing to the significant increase in vertical seismic response is the increase in the vertical input seismic motion from 0.2g to 0.4g, resulting in a maximum vertical seismic response ratio of 2.54 between the isolated and non-isolated structures. If the original vertical seismic motion target remains unchanged, additional measures such as vertical seismic reduction or three-dimensional isolation may be needed to further achieve the goal of improving the vertical ultimate safety ground motion. The displacement limitation of the isolation layer in nuclear island buildings is often a critical control factor in isolation design. The development of high-performance lead rubber bearings has significant positive implications for such projects.